(untitled) (Ustozlar uchun, 2024)
Abstract: in this scientific article, it is known that in the development of all areas, it is important to have a strong legal basis and create opportunities for sufficient activity. Based on this, it was considered that sufficient legal bases for the activity of stock exchanges in the Republic of Uzbekistan have been strengthened.